Room temperature phosphorescence of the 1-bromonaphthalene/b-cyclodextrin inclusion complex: comparison between right-angle and front-face illumination geometry - Pacheco, Maria Emilia (2013)
The importance of correction for inner filter effects has been demonstrated in the case of the widely studied 1-bromonaphthalene/ b-cyclodextrin inclusion complex by means of right-angle and front-face illumination geometry.